The Nabokov Effect - Jottkandt, Sigi (Open Humanities Press, 2024)
Sigi Jöttkandt's The Nabokov Effect: Reading in the Endgame attends to the ‘lettrocalamity’ that occurs when literature and cinema collide in Vladimir Nabokov’s work. Jöttkandt suspends the long-held critical investment in Nabokov’s authorial control to focus on another principle of representational agency making incursions into his books. Tracing the subterranean network of cross-lingual puns, homophonies, and technical overflows of writing to a cinaesthetic signature system, Jöttkandt recasts the vexed question of Nabokov’s relation to psychoanalysis. A pioneer of too-close reading, Nabokov offers himself, Jöttkandt argues, as the tipping point of perceptual and epistemological systems that are in the process of devouring themselves. The ensuing ‘Nabokov effect’ is both an assault on teleological models, and an opening onto other forms of reading and listening, which Jöttkandt argues was always latent in psychoanalysis. In this book, Nabokov emerges as the writer for humanity’s endgame, architect of a post- interpretive complex that opens up broader questions concerning our ability to read him or, indeed any writer, today.